Hats and tarbooshes: identity, cosmopolitanism, and violence in 1920s Alexandria - Woodward, Daniel (AUC Knowledge Fountain, 2014)
In May of 1921 Alexandria was consumed by demonstrations against the British-backed Adly Cabinet. In a matter of days these protests developed into violence which targeted people based on perceived communal affiliation. In total, 88 people were killed and 238 were wounded. Through a detailed examination of this communal and political violence, a moment that has largely be left out of the Egyptian historical narrative, I provide a greater understanding of how the complex dynamics of identity and power operated in Alexandrian society in this crucial period in the formation of the narrative of Egyptian identity. Utilizing a variety of primary and secondary sources, I use this moment to complicate both the romantic cosmopolitan narrative which has dominated much of Alexandrian historiography and the anti-colonialist narrative of 1950s nationalism. The cosmopolitan narrative is flawed because it ignores or celebrates the inherently exploitative colonial structure of early twentieth century Egypt and, as I show using court records, relies on simplistic understandings of identity in Alexandrian society. Many anti-colonial narratives rely on similarly simplistic understandings of identity. Ultimately the goal of this thesis is to use a specific incident to explore and complicate the dominant narratives of the historiography of Alexandria.